2016
DOI: 10.1161/strokeaha.115.012170
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Hematoma Volume Measurement Error in Intracerebral Hemorrhage

Abstract: Background and Purpose-Limiting intracerebral hemorrhage (ICH) and intraventricular hemorrhage (IVH) expansionis a common target for acute ICH studies and, therefore, accurate measurement of hematoma volumes is required. We investigated the amount of hematoma volume difference between computed tomography scans that can be considered as measurement error. Methods-Five raters performed baseline (<6 hours) and 24-hour total hematoma (ICH+IVH) computer-assisted volumetric analysis from 40 selected ICH patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…We demonstrated excellent inter-rater and intra-rater ICCs in both Analyze and Osirix using a validated semi-automated planimetry approach [10]. The reliability of the ICH measurement in our study is consistent with that reported in the literature (inter-rater and intra-rater ICCs >0.900) [12,14,18]. Divani et al demonstrated in a simulated cadaveric ICH model that Analyze software and Medical Imaging Processing, Analysis and Visualization (Center for Information Technology, National Institutes of Health, Bethesda, MD) software produced less error than the ABC/2 method when compared to the actual volume of simulated blood injected, but the authors did not directly compare the volumes produced by the different softwares [19].…”
Section: Reliability Of Semi-automated Planimetrysupporting
confidence: 87%
“…We demonstrated excellent inter-rater and intra-rater ICCs in both Analyze and Osirix using a validated semi-automated planimetry approach [10]. The reliability of the ICH measurement in our study is consistent with that reported in the literature (inter-rater and intra-rater ICCs >0.900) [12,14,18]. Divani et al demonstrated in a simulated cadaveric ICH model that Analyze software and Medical Imaging Processing, Analysis and Visualization (Center for Information Technology, National Institutes of Health, Bethesda, MD) software produced less error than the ABC/2 method when compared to the actual volume of simulated blood injected, but the authors did not directly compare the volumes produced by the different softwares [19].…”
Section: Reliability Of Semi-automated Planimetrysupporting
confidence: 87%
“…However, these methodological limitations applies to both, OAC-ICH and non-OAC-ICH. (5) Even with sophisticated measuring techniques, for large haematomas, the magnitude of haematoma volume measurement error may exceed the threshold used to dichotomize HE in the respective study [43]. In our analysis of aggregate data, we were not able to correct for this incertitude.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previous studies have indicated, an absolute definition of >6 ml falls within the MDD for total haematoma volume. 24 Furthermore, the requirement for follow-up imaging to assess for haematoma expansion likely excluded patients at highest risk of early mortality, which precluded our ability to fully determine the effect of haemorrhage location on clinical outcome. Our choice to exclude patients who received a ventricular drain prior to repeat imaging may have biased our sample towards better outcomes.…”
Section: Discussionmentioning
confidence: 99%